Enhanced tribological and mechanical properties of polybutylene terephthalate nanocomposites reinforced with synthetic wollastonite nanofibers/graphene oxide hybrid nanofillers - Othman, Norhayani; Jia, Xin Chan; Joon, Fatt Wong; Hassan, Azman; Abd Razak, Jeefferie; Nirmal, Umar; Hashim, Shahrir; Yern, Chee Ching; Yunos, Muhamad Zaini; Sampath Udeni Gunathilake, Thennakoon M. (Elsevier Ltd., 2023)
Polybutylene terephthalate (PBT) hybrid nanocomposites reinforced with hybrid synthetic wollastonite nanofibers (SWN)/graphene oxide (GO) were successfully prepared by melt compounding. The present work studied the effect of GO content on the structural, morphological, mechanical, thermal and tribological properties of PBT/SWN/GO hybrid nanocomposites. GO dispersion in the hybrid nanocomposites was improved through the bridging between SWN and GO nanofillers. Hybridization of nanofillers synergistically enhanced the Young's modulus of hybrid nanocomposites up to 1.34 GPa. However, due to the poor interaction of GO with PBT matrix, the stress transfer within the hybrid nanocomposites was impeded, while the reinforcing effect of SWN were offset. Thus, the tensile strength fluctuated around 52 MPa. The optical analysis revealed that the hybridization of SWN and GO improved the tribological properties of hybrid nanocomposites by significantly promoting the formation of transfer film at the sliding interface. The wear mechanism of the PBT hybrid nanocomposite containing 2.0 phr GO titled from a combination of adhesive and abrasive wear to severe abrasive wear due to the presence of abrasive third-body. The incorporation of 1 phr SWN and 1.5 phr GO exhibited the highest enhancement in Young's modulus (16 %), crystallization temperature (5.7 °C), thermal stability (17.1 °C), wear resistance (43 %) and anti-friction properties (34 %) among the hybrid nanocomposites. This study explores the potential of hybrid SWN/GO nanofillers for developing advanced tribomaterials in the automotive industry.